Complement factor H levels are decreased and correlated with serum C-reactive protein in late-onset Alzheimer's disease - LU, Guo; LIU, Weihong; HUANG, Xinying; ZHAO, Yanxin (Arquivos de Neuro-Psiquiatria, 2020)
Alzheimer’s disease (AD) is the most common cause of dementia. Despite numerous studies on the subject, the pathologies for AD are still unclear and there is still no ideal biomarker for diagnosis. The present study aimed to investigate clinical significance of human complement factor H (CFH) in patients with late-onset AD. Methods: The present prospective study included 187 late-onset AD patients who went to our hospital from January 2015 to December 2017. One hundred patients with mild cognitive impairment (MCI) and 80 healthy individuals who were age and gender matched to AD patients were enrolled as controls. Demographic data such as age, gender, and education duration were recorded. Blood samples were collected and serum levels of C-reactive protein (CRP), CFH, and brain-derived neurotrophic factor (BDNF) were determined by Enzyme-linked immunosorbent assay (ELISA). The mini-mental state examination (MMSE) score was measured for all patients. Results: No significant difference was found in age, gender, and education duration for all participants. The MMSE scores showed AD patients had lower MMES scores than the other two groups. All factors of CFH, CRP, and BDNF were dramatically decreased in AD patients compared with the MCI and the ealthy control. Levels of CFH were found to be positively correlated with levels of CRP; however, no significant correlation was found between CFH and BDNF, nor CFH and MMSE. Conclusion: CFH was decreased in late-onset AD patients, and serum levels of CFH was correlated with serum levels of CRP, but not MMSE and BDNF. These results may provide more clinical evidences for the role of CFH in AD patients.
Keywords: complement factor H; late-onset Alzheimer's diseases; C-reactive protein